The unrealised potential for transformative reparations for sexual and gender-based violence in Sierra Leone. Issue 9 (22nd November 2017) - Williams, Sarah; Opdam, Jasmine
ABSTRACT: The conflict in Sierra Leone was known for the scope and severity of atrocities targeted at civilians, including sexual and gender-based violence (SGBV) mainly perpetrated against women and girls. Post-conflict initiatives included the establishment of a hybrid criminal tribunal, the Special Court for Sierra Leone (SCSL), and a truth and reconciliation commission (TRC). However, neither possessed a mandate for reparations to victims, yet both have made some contribution to tranformation. The judgments and processes of the SCSL have provided a measure of recognition to victims of SGBV. The TRC was required to to pay special attention to the experiences of women and girls in respect of sexual violence and structural inequality. It also interpreted its mandate broadly, in particular to making general recommendations as to the position of women and girls, as well as more specific recommendations as to reparations projects. These recommendations addressed three aspects of gender justice based on Fraser (recognition, representation and redistribution) and offered considerable scope for transformative reparations for victims of SGBV, including through structural, legal and social changes intended to guarantee the non-repetition of sexual violence. However, this article argues that although several of the TRC's recommendations had transformative potential, much of this potential has not been realised due to the failure of the government to implement those recommendations.